Quality of Life among CKD Patients with Hemodialysis – A Cross-Sectional Study - Begum, Shaik Shafiya; Shamsuzzaman, Md. (Journal of Neonatal Surgery, 2025)
Objectives: To assess quality of life (QOL) of patients undergoing Hemodialysis (HD) Methods: A Cross sectional study was conducted among 461 subjects for a period 7 months at the dialysis unit, Guntur, South India, KDQOL-SF1.3 scale was used. Ethical committee permission (IEC/AMSH/2023/20) was obtained for the conduction of study. Results: Total sample were 461 from that males (56%) were more than females (43.8%) respectively rural area 267(57.92) while subjects from urban area 194(42.08). Majority of the subjects are graduates who are 153(33.19%) followed by those who have completed their secondary education is 137(29.72%). It is understood that patients who have comorbidities from 5 to 10 years are 156(33.84) followed by10 to 15 years are more i.e. 145(31.45). Majority of the patients undergoing Hemodialysis are known to have poor nutrition levels 225(48.81Most of the subjects are in anemic condition 323(70%) whose Haemoglobin levels were found to be between 5-10g/dL. Majority of the patients 247(77.62) complained of fatigue. The SF12 subscale shows moderate scores, while burden of kidney disease scores exhibits higher variability. Stage III CKD patients exhibited the highest scores, particularly in symptoms and effects of kidney disease subscales, whereas stage V CKD patients had the lowest scores across all subscales. Conclusion: The current study findings conclude that, the patients on Hemodialysis are not having adequate QOL (Quality of Life) in all the domains except patient satisfaction due to the variation in physio-chemical changes occurring in the blood chemistry which provides relief to the patient.